Peran Kepala Sekolah Terhadap Kebijakan Pendidikan Inklusi di Tingkat Sekolah Dasar - Luk Luk Yata Lalak Muslimin; Muqowim Muqowim (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to reveal the role of school principals in inclusive education policies at the elementary school level. This research method uses a descriptive method with a qualitative approach. The subjects of this study were principals, teachers, and guardians of students at SDN 20 Mataram. Data collection techniques in this study used interviews, observation, and documentation. Meanwhile, the data analysis technique used descriptive qualitative analysis. The results of this study are the principal's role by making changes and making policies that support the implementation of inclusive education in planning, process, and evaluation. The supporting and inhibiting factors of the principal's policy on inclusive education include the positive attitude of accepting students with special needs from the principal, teachers, and education staff without any difference. Second, there is additional funding provided by the government. Third, flexible school curriculum. Fourth, there are supporting facilities and infrastructure as well as learning resources. Fifth, the location of the school adjacent to the SLB. In contrast, the inhibiting factor is the absence of a special assistant teacher at SDN 20 Mataram.